FIRST Th-U-Pb SINGLE ZIRCON DATING OF METASOMATITES FROM THE BELOMORIAN MOBILE BELT - Serebryakov N.S.; Astaf'ev B.Y.; Voinova O.A.; Presnyakov S.L. (My University, 2007)
Metasomatites have long been known among the rocks of the Belomorian mobile belt (BMB). These rocks are distributed over the entire belt as relatively small lenslike or vein-shaped bodies restricted to the local shear zones. The metasomatites are most abundant in the Chupa sequence of the BMB and at its junction with the Karelian Craton. Study of the formation conditions and localization of the metasomatites is of great significance for deciphering endogenous activity within the BMB, elucidating the fluid regime during metamorphism, detection of deep-seated and other conduits for fluid circulation, and discovery of ore objects among the metamorphic rocks of the belt. The BMB has a long-term intricate evolution related to repeated deformations, polymetamorphism, and multiple emplacements of the magmatic melts. Therefore, it is necessary to determine the age of the metasomatic process in this belt. The aim of this paper was to carry out the Th–U–Pb single zircon dating of metasomatic rocks of the BMB.